Intelligence correlates with the temporal variability of brain networks. (10th November 2022) - Shi, Manqing; Li, Yu; Sun, Jiangzhou; Li, Xinyi; Han, Yurong; Liu, Zeqing; Qiu, Jiang
Highlights: Few studies have evaluated the relationship between brain dynamics and intelligence. Dorsal attention network temporal variability positively correlated with performance intelligence. Salience network temporal variability positively correlated with performance intelligence. Abstract: Intelligence is the ability to recognize and understand objective things, and use knowledge and experience to solve problems. Highly intelligent people show the ability to switch between different thought patterns and shift their mental focus. This suggests a link between intelligence and the dynamic interaction of brain networks. Thus, we investigated the relationships between resting-state dynamic brain network remodeling (temporal variability) and scores on the Wechsler Adult Intelligent Scale using a large dataset comprising 606 individuals. We found that performance intelligence was associated with greater temporal variability in the functional connectivity patterns of the dorsal attention network. High variability in these areas indicates flexible connectivity patterns, which may contribute to cognitive processes such as attention selection. In addition, performance intelligence was related to greater temporal variability in the functional connectivity patterns of the salience network. Thus, this study revealed a close relationship between performance intelligence and high variability in brain networks involved in attentional choice, spatial orientation, and cognitive control.